Evaluation of the clinical characteristics and survival outcomes of invasive pulmonary aspergillosis patients - Qiangsheng Feng; Xiaoqin Ha; Yuejuan Song (Frontiers in Microbiology)
BackgroundInvasive pulmonary aspergillosis (IPA) is a severe infectious disease caused by Aspergillus spp. It is associated with high mortality, particularly in immunocompromised patients, as well as in those with COVID-19 pneumonia or critically ill individuals in intensive care units (ICUs). Accurate clinical diagnosis remains a significant challenge, often resulting in missed diagnoses.MethodsThis study evaluated IPA inpatients diagnosed through mycological evidence and clinical criteria over 12 months. Inclusion criteria required at least one positive mycological result, including a positive culture from bronchoalveolar lavage fluid (BALF) or high-quality sputum, or a positive galactomannan antigen (GM) test.ResultsA total of 216 patients were diagnosed with IPA, with a mortality rate of 68.5%. Hematologic malignancies were the primary underlying condition in 33.8% of cases. Voriconazole or posaconazole was used in 45% (98/216) of patients overall, but only 26% (32/121) of non-hematologic malignancy patients received these treatments. The 28-day survival rate for patients treated with Voriconazole/Posaconazole was 0.776 ± 0.038, compared to 0.421 ± 0.043 for untreated patients. Median survival was 130 days (95% CI, 35.3–224.7) for treated patients vs. 20 days (95% CI, 15.8–24.2) for untreated patients (p < 0.001). Biomarkers for IPA diagnosis demonstrated high diagnostic value, with area under the curve (AUC) values for GM, G, PCT, IL-6, WBC, NEU%, and D-dimer of 0.953, 0.983, 1.000, 0.999, 0.961, 0.996, and 1.000, respectively. GM levels >0.5 pg/ml had a positive predictive value of 52.9% (27/51), while positive mycological culture had a predictive value of 46.5% (33/71). Multivariable regression analysis identified several significant factors associated with in-hospital mortality: IPA (OR 7.509, 95% CI 4.227–13.339, p < 0.001), Voriconazole/Posaconazole treatment (OR 0.124, 95% CI 0.063–0.242, p < 0.001), ICU hospitalization (OR 5.280, 95% CI 1.549–18.002, p = 0.008), hematologic malignancy (OR 0.316, 95% CI 0.174–0.573, p < 0.001), and NEU% ≥87.25% (OR 3.409, 95% CI 1.455–7.990, p = 0.005).ConclusionNon-hematologic malignancy patients with IPA were frequently undertreated with antifungal therapy. A comprehensive diagnostic approach using biomarkers, CT, mycological evidence is crucial. Key risk factors for mortality include lack of Voriconazole/Posaconazole treatment, IPA diagnosis, ICU admission, non-hematologic malignancies, and elevated NEU%.